DEVELOPING INCREASING TEACHER PERFORMANCE ON STUDENT LEARNING MOTIVATION - Dina Destari (International Journal of Teaching and Learning, 2024)
Teacher performance is an important thing that must be of concern to teachers and related parties, teachers must have good performance, good or bad teacher performance influences the learning outcomes achieved by students, because teachers are central figures in serving student education in schools, from science teachers flows into the student, and from the teacher's performance the student's personality and achievements are formed. Efforts that school principals can make to improve teacher performance are: 1) Fostering teacher performance, 2) Monitoring teacher performance, 3) Providing motivation, 4) Evaluating teacher performance. Teacher performance can be seen and measured based on competency specifications/criteria that must be possessed by every teacher, which can be displayed through mastering pedagogic, professional, personality and social competencies. Teacher performance has a significant contribution to student learning motivation. This can be proven from the trend of teacher performance and learning motivation, the results of which show that teachers who have very high and high performance have students with very high learning motivation.